2013
DOI: 10.1590/s1984-29612013000400025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and parasitological detection ofLeishmania spp. in a dipteran of the speciesTabanus importunus

Abstract: Leishmaniasis is an important chronic zoonosis caused by protozoa of the genus Leishmania spp. The major vectors of this protozoosis are sand flies, and Lutzomyia longipalpis is considered the main species implicated in the transmission of American Visceral Leishmaniasis in Brazil. The presence of the parasite's deoxyribonucleic acid (DNA) in ectoparasites such as ticks and fleas has prompted speculations about the existence of new vectors in the cycle of leishmaniasis. The aim of this paper is to report the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This fact is noteworthy, given the fact that, in another study by Coelho et al ( Coelho and Bresciani, 2013 ) in the same municipality, the occurrence of coinfection by T. evansi and Leishmania was observed in a dog from the rural area. No phlebotomine sand flies were captured in this region, but it is an area with a high occurrence of horseflies, stable flies, mosquitoes and black flies.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This fact is noteworthy, given the fact that, in another study by Coelho et al ( Coelho and Bresciani, 2013 ) in the same municipality, the occurrence of coinfection by T. evansi and Leishmania was observed in a dog from the rural area. No phlebotomine sand flies were captured in this region, but it is an area with a high occurrence of horseflies, stable flies, mosquitoes and black flies.…”
Section: Discussionmentioning
confidence: 66%
“…The presence of amastigote forms of Leishmania spp. in a horsefly in this area was also reported for the first time ( Coelho and Bresciani, 2013 ).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…A specimen of Tabanus importunus was found infected with a Leishmania sp. : the diagnosis was performed using DNA amplification technique, in São Paulo, Brazil [186]. Borrelia burgdorferi was found naturally infecting tabanids on Marambaia Island, Rio de Janeiro, southeast Atlantic Brazilian Forest (no published data from Guimarães et al).…”
Section: Tabanids and Diseasesmentioning
confidence: 99%
“…Conversely, the study by Paz et al (2010) concluded that it was unlikely that Leishmania maintenance and multiplication occurs within R. sanguineus. Our research group has focused upon the study of the epidemiology and diagnosis of canine visceral leishmaniasis, with an interest in the role nontraditional vectors might have in the biological cycle of this disease (Coelho and Bresciani 2013). We utilized immunohistochemistry (IHC) and PCR to test for the presence and prevalence of Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%